Development of Smart Apps Creator Interactive Learning Media to Improve Student Learning Outcomes in Grade 4 Elementary School Science Learning - Sari, Ulum Rohma; Sumarmi, Sumarmi; Susiswo, Susiswo (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research is Research and Development (RD). Development is carried out by referring to the Borg and Gall model with stages of information gathering, planning, initial draft development, expert feasibility trials, product revision resulting from expert trials, small group trials, revision of small group trial results, field trials, revisions and product improvements. This development research aims to analyze the results of the learning media that have been developed, analyzing the use of interactive learning media that have been developed in improving student learning outcomes. The instruments used in this research were learning media validation, a media practicality assessment questionnaire and student pretest and posttest questions. Media eligibility criteria are seen from the practical aspects of ease of use of media and effectiveness in improving student learning outcomes. Based on the results of the research analysis, it can be concluded that the smart apps creator learning media is suitable for use and meets practicality criteria. Based on the pretest and posttest results, it was concluded that learning using smart apps creator media was very effective in improving student learning outcomes.